Geoenvironmental Disasters - Wang, Fawu
Geoenvironmental Disasters is an international journal with a focus on multi-disciplinary applied and fundamental research and the effects and impacts on infrastructure, society and the environment of geoenvironmental disasters triggered by various types of hazards (e.g. earthquakes, volcanic activity, landslides, tsunamis, intensive erosion and hydro-meteorological events). The integrated study of Geoenvironmental Disasters is an emerging and composite field of research interfacing with areas traditionally within civil engineering, earth sciences, atmospheric sciences and the life sciences. It centers on the interactions within and between the Earth's ground, air and water environments, all of which are affected by climate, geological, morphological and anthropological processes; and biological and ecological cycles. Disasters are dynamic forces which can change the Earth pervasively, rapidly, or abruptly, and which can generate lasting effects on the natural and built environments. The journal publishes research papers, case studies and quick reports of recent geoenvironmental disasters, review papers and technical reports of various geoenvironmental disaster-related case studies. The focus on case studies and quick reports of recent geoenvironmental disasters helps to advance the practical understanding of geoenvironmental disasters and to inform future research priorities; they are a major component of the journal. The journal aims for the rapid publication of research papers at a high scientific level. The journal welcomes proposals for special issues reflecting the trends in geoenvironmental disaster reduction and monothematic issues. Researchers and practitioners are encouraged to submit original, unpublished contributions. The research topics covered by the journal include, but are not limited to, the following fields: Natural hazards as potential for geoenvironmental disasters Understanding the impacts of geoenvironmental disasters Community geoenvironmental disaster mitigation, preparedness, response to and recovery from geoenvironmental disaster events Development of analytical instruments, modeling and methods for geoenvironmental disaster reduction New proxies and lab techniques for geoenvironmental disaster risk reduction Remote sensing tools and techniques for geoenvironmental disaster observation and mitigation GIS techniques for geoenvironmental disaster management Impact of geoenvironmental disasters in urban and rural infrastructures Geoenvironmental disaster database and knowledge sharing Climate and environmental changes and geoenvironmental disaster mitigation Management of geoenvironmental disasters in scarce population environment Anthropogenic controls on geoenvironmental disasters Social and economic impacts of geoenvironmental disasters Resilience of environmental systems to the global change and extreme events Impact of geoenvironmental disasters on heritage and conservation areas Geoenvironmental disaster adaptation and risk perception Engineering designs for geoenvironmental disaster mitigation Low cost, environment friendly and sustainable geoenvironmental disaster mitigation practices Early warning of geoenvironmental disaster events Theoretical aspects of geoenvironmental disaster studies and prognosis Any other important new application or theories on geoenvironmental disasters that not listed here.